2020
DOI: 10.1016/j.seizure.2020.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological outcomes after pediatric epilepsy surgery: Role of electrical stimulation language mapping

Abstract: We studied the association between electrical stimulation mapping (ESM) with a visual naming task and post-operative neuropsychological outcomes after pediatric epilepsy surgery. Methods: Children who underwent epilepsy surgery, having pre-and 1-year post-surgery neuropsychological evaluation (NPE) available, were included. NPE scores were transformed using principal components (PC) analysis. The relationship between post-surgical PC scores, adjusted for pre-surgery PC scores, and ESM was analyzed. Clinical va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…ESM can also help anticipate and prepare for post-operative deficits if there is an overlap between the seizure-onset zone and eloquent functional regions. With SDE, although earlier studies were somewhat discordant (Lendt et al, 1999;de Koning et al, 2009;Skirrow et al, 2011;Puka et al, 2017), a recent large study has demonstrated the relationship between ESM and neuropsychological outcomes (Sakpichaisakul et al, 2020). A multi-center study with sufficient sample size, using valid and comprehensive age-appropriate assessments, both pre-and post-operatively, to establish the predictive value of SEEG ESM for neurological outcomes is imminently needed.…”
Section: Conclusion and Avenues For Future Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…ESM can also help anticipate and prepare for post-operative deficits if there is an overlap between the seizure-onset zone and eloquent functional regions. With SDE, although earlier studies were somewhat discordant (Lendt et al, 1999;de Koning et al, 2009;Skirrow et al, 2011;Puka et al, 2017), a recent large study has demonstrated the relationship between ESM and neuropsychological outcomes (Sakpichaisakul et al, 2020). A multi-center study with sufficient sample size, using valid and comprehensive age-appropriate assessments, both pre-and post-operatively, to establish the predictive value of SEEG ESM for neurological outcomes is imminently needed.…”
Section: Conclusion and Avenues For Future Researchmentioning
confidence: 99%
“…While epilepsy surgery can improve executive function and memory in some patients, probably by removing the pathological effects of seizures and epileptiform discharges, more frequently it is associated with a decline in verbal memory, naming, attention, and other domains (Lendt et al, 1999;de Koning et al, 2009;Ives-Deliperi and Butler, 2012). The neuropsychological outcomes after epilepsy surgery are driven by multiple factors, including but not limited to the age at onset of seizures, age at the time of surgery, anti-seizure medications, presence and nature of an epileptogenic lesion, location of the seizure-onset zone, its relationship with the eloquent cortices, neurosurgical planning, and most importantly, post-operative seizure outcomes (Skirrow et al, 2011;Puka et al, 2017;Sakpichaisakul et al, 2020). Whether pre-surgical ESM reduces the risk of adverse postoperative outcomes, over and above what may be expected from demographic and clinical information, remains a vexing question.…”
Section: Esm and Post-operative Outcomesmentioning
confidence: 99%
See 3 more Smart Citations